How do students deal with the uncertainty of sustainability challenges? Metacognitive learning in a transdisciplinary course - Bohm, Nina L.; Klaassen, Renate G.; van Bueren, Ellen; den Brok, Perry (Frontiers in Education, 2024)
While tackling sustainability challenges, engineering students confront various uncertainties, including the unpredictability of real-world scenarios, unfamiliar aspects of problems, and conflicting viewpoints among stakeholders. Despite previous research indicating the likelihood of encountering such uncertainties in sustainability projects, it is unclear if students are aware of uncertainty and what specific regulatory behaviors they develop to address them. This study seeks to deepen our understanding of the awareness and regulation of uncertainty by students while they work on real-life sustainability challenges. To achieve this, we observed nine MSc students enrolled in a transdisciplinary course on urban sustainability at a Dutch university of technology. Through interviews, we explored the uncertainties they faced and how they navigated them. Our analysis, conducted through open, consensus-based coding by two researchers, revealed that students primarily encountered the uncertainty of multiplicity, characterized by divergent stakeholder perspectives. Additionally, students increasingly recognized the inherent unpredictability of the challenges over the course. To address uncertainty, students developed three kinds of behaviors to deal with uncertainty: seeking social support from commissioners, coaches, and peers; employing small coping mechanisms to overcome obstacles; and developing attitudes such as empathy, flexibility, and relativism. This study offers detailed insights into how students navigate uncertainty. Moving forward, efforts in uncertainty education should prioritize how educators can positively influence the development of metacognition in uncertainty.